Combining MPDL3280A with adoptive cell immunotherapy exerts better antitumor effects against cervical cancer. Issue 4 (4th July 2017) - Zheng, Yi; Yang, Yicheng; Wu, Shu; Zhu, Yongqiang; Tang, Xiaolong; Liu, Xiaopeng
ABSTRACT: As the second most common gynecologic malignant tumors with a high mortality rate, cervical cancer jeopardizes women's life worldwide. The low cure rate in cervical cancer patients is mainly attributed to the lack of effective therapies. One feasible novel strategy is to develop immune-based approaches such as adoptive cell immunotherapy of DCCIKs which represents a promising nontoxic antineoplastic immunotherapy preferred in clinic practice. However, the therapeutic effect is not as efficient as anticipated. Possible explanations are tumors exploit immunoregulatory check-points such as programmed death 1(PD1)/PDL1 which provides tumor cells an escape strategy of circumventing immunologic rejection from immune surveillance by hampering activated tumor-specific T cell activities and rendering them functionally exhausted. With reduced transformation activity and enhanced antigenicity, a modified HPV16 E7 (HPV16mE7) was used to load DCs with silenced SOCS1 mediated by a recombinant adenovirus to improve the targetability and efficiency against cervical cancer. Combined with anti-PDL1 antibody MPDL3280A therapy, the co-cultured DCCIKs were transfused into murine models bearing tumor of HPV16 E6/E7 expressing CaSki cells for in vitro/in vivo antitumor activity assay. Although all of the animals succumbed to CaSki tumors even after adoptive DCCIKs transfer or MPDL3280A immunotherapy, the infusion of PDL1 blocking monoclonal antibody with activated T cells cured 40% of animals. These data support PDL1 blockade improves the efficacy of adoptive DCCIKs therapy, providing a new approach of immunotherapy against cervical cancer.